Changes in Back Compressive Force When Measuring Maximum Acceptable Weight of Lift in Iranian Male Students - Ali SALEHI SAHL ABADI; Gebraeil NASL SARAJI; Adel MAZLOUMI; Hojjat ZERAATI; Mohammad Reza HADIAN; Amir Homayoun JAFARI (Tehran University of Medical Sciences, 2016)
Background: Low back pain caused by work, ranked the second after cardiovascular diseases, are among the most common reasons of patients' referral to the physicians in Iran. This study aimed to determine the changes in back compressive force when measuring maximum acceptable weight of lift in Iranian male students. Methods: This experimental study was conducted in 2015 on 15 young male students were recruited from Tehran University of Medical Science. Each participant performed 18 different lifting tasks involving three lifting frequencies, with three lifting heights, and two box sizes. Each set of experiments was conducted during the 20 min work period using free-style lifting technique. The back compressive force evaluated with hand-calculation back compressive force method. Finally, Pearson correlation test, analysis of variance (ANOVA) and t-test were used for data analysis. Results: The mean of back compressive force (BCF) for the small and large boxes at a frequency of 1lift/min at heights of F - K height, were 1001.02 (±86.74), 1210.57 (±93.77) Ib, respectively. There was a significant difference between mean BCF in terms of frequencies of lifts (P=0.02). The result revealed significant difference between frequencies of 1 lift/min and 6.67 lift/min (P=0.01). There was a significant difference between mean BCF in terms of the sizes of the two boxes (P=0.001). There was a significant relationship between the BCF and maximum acceptable weight of lift in all test conditions (P=0.001). Conclusion: BCF is affected by box size, lifting frequency and weight of load.   Keywords: Back compressive force, Maximum acceptable weight of lift, Psychophysical methodology